Patient Safety in Intraoperative current Nursing Skills - Ângelo, Sónia Ventura (2017)
Patient safety is an issue that has assumed increasing importance, with the World Health Organization, resulting in concern and the adoption of simple measures of universal character. In the operating room there is a high prevalence of adverse events, and safety of the surgical environment and maintenance functions performed by nurses in the perioperative period. It is considered the circulating nurse, a professional with specific tasks in promoting the safety of the patient and other professionals, defined as objectives: to identify the existence of a safety culture by circulating nurses of operating theater of a hospital; observe the procedures of circulating nurse during surgery; see if the circulating nurse meets the standards issued by the competent authorities for patient safety in the Operating Room; identify procedures or practices carried out by circulating nurses, which can cause damage to the patient; propose strategies on the performance of nurses who seek to make gains in the health of the patient. We developed a quantitative, descriptive and correlational. Information was obtained through the application of two instruments, a questionnaire and a grid point. The sample, not probabilistic rational choice, was selected from the population of nurses (74) of the operating theater of a hospital; it consisted of 50 circulating nurses. It was found that participants show an adequate knowledge about the existence of a safety culture in the Operating Room identifying aspects to improve, it was observed that most performed practices comply with the rules issued by the competent authorities; however they were recognized some weaknesses and gaps to change. Find solutions to overcome these weaknesses, adopting practices and procedures that promote improved safety and quality of care to the surgical patient are the commitment of circulating nurses.